Microtubule dysfunction precedes transport impairment and mitochondria damage in MPP⁺-induced neurodegeneration - Cartelli, Daniele; Ronchi, Cristina; Maggioni, Maria G; Rodighiero, Simona; Giavini, Erminio; Cappelletti, Graziella (Journal of neurochemistry, 2010)
J. Neurochem. (2010) 115, 247-258. Dysfunction of the microtubule (MT) system is an emerging theme in the pathogenesis of Parkinson's disease. This study was designed to investigate the putative role of MT dysfunction in dopaminergic neuron death induced by the neurotoxin 1-methyl-4-phenylpiridinium (MPP⁺). In nerve growth factor-differentiated PC12 cells, we have analyzed post-translational modifications of tubulin known to be associated with differently dynamic MTs and show that MPP⁺ causes a selective loss of dynamic MTs and a concomitant enrichment of stable MTs. Through a direct live cell imaging approach, we show a significant reduction of MT dynamics following exposure to MPP⁺ and a reorientation of MTs. Furthermore, these alterations precede the impairment of intracellular transport as revealed by changes in mitochondria movements along neurites and their accumulation into varicosities. We have also analyzed activation of caspase 3 and mitochondrial injury, well-known alterations induced by MPP⁺, and found that they are noticeable only when MT dysfunction is already established. These data provide the first evidence that axonal transport impairment and mitochondrial damage might be a consequence of MT dysfunction in MPP⁺-induced neurodegeneration, lending support to the concept that alterations of MT organization and dynamics could play a pivotal role in neuronal death in Parkinson's disease.